Preliminary study oceanography and environmental parameters of habitat endemic species Halmahera walking shark (Hemiscyllium halmahera) on Indopacific Ocean Area in North Maluku Indonesia - Nyoman Metta N Natih; Nebuchadnezzar Akbar; Dietriech G Bengen; I Wayan Nurjaya; Riyadi Subur; Abdurrachman Baksir; Firdaut Ismail; Iswandi Wahab; Dondy Arafat; Rustam E Paembonan; Abdul Ajiz Siolimbona; Rasidi Rasidi; Asep Sandra Budiman; Beginer Subhan (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
The Halmahera Walking Shark (Hemiscyllium halmahera) is an endemic species in the Halmahera Sea. Information related to the environment in general has not been described in a complex manner. The environment is the main factor to support the life of biota. Environmental characteristics are a determining factor in the sustainability of biota. The study aims to provide information related to the physical environment of the habitat of the H. halmahera species. Primary data collection was carried out directly (in situ). Current data was taken using the Lagrange method using a currents drogue. Tides using tidal palms and observed for 24 hours. Secondary data was taken from Marine Copernicus and the Geospatial Information Agency (BIG). All data were tabulated and analyzed by Ocean Data View (ODV) software. The results of the study found that the surface current velocity was found to be in the fast current category. Current speed descriptively provides information on the life of H. halmahera. Primary data shows that the direction of the surface current moves to the east and north. Secondary data in vertical distribution shows weak zonal and meridional current shifts. The tidal pattern was found to be two high and low tides (semidiurnal). The distribution of surface temperature was found to be around 30-32oC. The vertical temperature profile found three layers, namely 1-13m (30oC), 65m (25oC) and 71m (20oC). The chemical environment showed all normal variables. The physical and chemical environmental conditions support H. halmahera to inhabit the sea area of Morotai Island. The environmental description has provided a brief understanding of how the ecological role of the H. halmahera species. Management and sustainability of the environment in the future due to climate change can be done with information on habitat characteristics.Keywords:coral triangleHalmaheranicheNorth Malukutropical